Molecular mechanism of the Escherichia coli AhpC in the function of a chaperone under heat-shock conditions - Kamariah, Neelagandan (2018)
Peroxiredoxins (Prxs) are ubiquitous antioxidants utilizing a reactive cysteine for peroxide reduction and acting as a molecular chaperone under various stress conditions. Besides other stimulating factors, oxidative- and heat stress conditions trigger their ATP-independent chaperoning function. So far, many studies were intended to reveal the chaperoning mechanisms of the so-called sensitive Prxs of eukaryotes, which are susceptible to inactivation by over-oxidation of its reactive cysteine during H2O2 reduction. In contrast, the chaperone mechanisms of bacterial Prxs, which are mostly robust against inactivation by over-oxidation, are not well understood. Herein, comprehensive biochemical and biophysical studies demonstrate that the Escherichia coli alkyl hydroperoxide reductase subunit C (EcAhpC) acquires chaperone activity under heat stress. Interestingly, their chaperoning activity is independent of its redox-states but is regulated in a temperature-dependent manner. Data are presented, showing that oxidized EcAhpC, which forms dimers at 25 °C, self-assembled into high molecular weight (HMW) oligomers at higher temperatures and supressed aggregation of client proteins at heat-shock conditions. In addition, we unravelled the essential role of the C-terminal tail of EcAhpC on heat-induced HMW oligomer formation and chaperoning activity. Our findings suggest a novel molecular mechanism for bacterial Prxs to function as chaperone at heat-shock conditions.